+0  
 
+1
50
1
avatar

simplify 12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

Guest Oct 25, 2017

Best Answer 

 #1
avatar+5229 
+1

12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

 

\(=\,12(\frac{3x-4}{3}-\frac{3-4x}{4}-\frac{6-2x}{6})\)

 

\(=\,\frac{(12)(3x-4)}{3}-\frac{(12)(3-4x)}{4}-\frac{(12)(6-2x)}{6} \\~\\ =\,\frac{(4)(3x-4)}{1}-\frac{(3)(3-4x)}{1}-\frac{(2)(6-2x)}{1} \\~\\ =\,(4)(3x-4)-(3)(3-4x)-(2)(6-2x) \\~\\ =\,12x-16 - 9+12x -12+4x \\~\\ =\,28x-37\)            Reduce the fractions.

hectictar  Oct 25, 2017
Sort: 

1+0 Answers

 #1
avatar+5229 
+1
Best Answer

12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

 

\(=\,12(\frac{3x-4}{3}-\frac{3-4x}{4}-\frac{6-2x}{6})\)

 

\(=\,\frac{(12)(3x-4)}{3}-\frac{(12)(3-4x)}{4}-\frac{(12)(6-2x)}{6} \\~\\ =\,\frac{(4)(3x-4)}{1}-\frac{(3)(3-4x)}{1}-\frac{(2)(6-2x)}{1} \\~\\ =\,(4)(3x-4)-(3)(3-4x)-(2)(6-2x) \\~\\ =\,12x-16 - 9+12x -12+4x \\~\\ =\,28x-37\)            Reduce the fractions.

hectictar  Oct 25, 2017

20 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details